2018
DOI: 10.1371/journal.pone.0201047
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of major depressive episodes and suicide-related ideation over a 3-year interval among Japanese undergraduates

Abstract: BackgroundSuicide has been a leading cause of death among young adult populations in Japan. The aim of this study was to predict major depressive episodes (MDEs) and suicide-related ideation among university students using the Patient Health Questionnaire-9 (PHQ-9) and the Temperament and Character Inventory (TCI).MethodsThe subjects were 2194 university students who completed the PHQ-9 and TCI in the 1st year (T1) and the PHQ-9 in the 4th year (T2) of university. Multiple logistic regression analysis was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 30 publications
3
38
0
Order By: Relevance
“…However, in previous studies of college and university students using the PHQ-9, the following were the depression prevalence (PHQ-9 ≥10) rates reported: 46.5% in the UK [ 17 ], 9.0% in China [ 18 ], 18.5% in Slovakia [ 19 ], and 31.7% in Ukraine [ 20 ]. Although a direct comparison between countries is difficult, within Japan, a study [ 14 ] investigating the pre-pandemic situation among 2194 students at one national university reported a 28.7% prevalence of depression (95% CI, 27–31) based on PHQ-9 scores ≥5. With the same diagnostic cutoff point (PHQ-9 ≥5), the prevalence of depression among our population reached 34% (95% CI, 33–37), indicating a statistically higher prevalence [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in previous studies of college and university students using the PHQ-9, the following were the depression prevalence (PHQ-9 ≥10) rates reported: 46.5% in the UK [ 17 ], 9.0% in China [ 18 ], 18.5% in Slovakia [ 19 ], and 31.7% in Ukraine [ 20 ]. Although a direct comparison between countries is difficult, within Japan, a study [ 14 ] investigating the pre-pandemic situation among 2194 students at one national university reported a 28.7% prevalence of depression (95% CI, 27–31) based on PHQ-9 scores ≥5. With the same diagnostic cutoff point (PHQ-9 ≥5), the prevalence of depression among our population reached 34% (95% CI, 33–37), indicating a statistically higher prevalence [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…For suicide-related ideation, question 9 of the PHQ-9, which encompasses thoughts of both suicide and self-harm [ 13 ], was used referring to previous literatures [ 14 , 15 ]. Participants were asked “Have you thought that you would be better off dead or of hurting yourself in some way?” The response received 0 for none, 1 for at least 2 days per week, 2 for at least 1 week, and 3 for nearly every day.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the prevalence of psychological distress among female medical students was 15%. It has been reported that the prevalence of major depressive episodes was 2.0% among Japanese undergraduates, as calculated by the Patient Health Questionnaire-9 (PHQ-9) [ 22 ], and 6.6% in the general female Japanese population aged 20–39 years, calculated using the Center for Epidemiological Studies Depression scale (CES-D) [ 23 ]. Moreover, the National Health and Nutrition Examination Survey (NHANES) revealed that the prevalence of depression symptoms was 7.4% in the general American population aged 18–39 years, as determined using the PHQ-9 [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were several studies on the predictors of depressive disorder in Japan. For instance, personality traits, such as self-directedness and harm avoidance, were significantly correlated with major depressive disorder in Japanese university students [20]. Negative automatic thought was found to be positively corelated with depression [21].…”
Section: Introductionmentioning
confidence: 93%